Mecanismos de reestenose coronária: estudo in vitro dos padrões de expressão gênica em células endoteliais e musculares lisas de artéria coronária humana - Camargo, Elaine Aparecida de [UNESP] (2015)
Percutaneous transluminal revascularization of coronary arteries (angioplasty) with bare-metal stents is the most widely used and successful medical intervention for treatment of coronary artery disease (CAD). However, the success of this procedure can be compromised by several events including endothelium injury, platelet deposition, inflammatory response and restenosis. With the advent of drug-eluting stents (DES), incidence of in-stent restenosis has decreased, but is still about 5% to 10%. Thus, this study aimed to investigate the molecular mechanisms underlying the initiation and development of in-stent restenosis. Cytotoxicity, genotoxicity and transcriptional alterations (gene expression profile) possibly induced by sirolimus, paclitaxel, colchicine and also by mechanical stress (cell stretching) were evaluated in human coronary artery endothelial (HCAEC) and coronary artery smooth muscle (HCASMC) cell lines. Acting at different phase of the cell cycle, the three drugs were equally effective for reducing cell proliferation in both cell lines. Nevertheless, while paclitaxel and colchicine induced apoptosis, the main mechanism of cell death induced by sirolimus was necrosis. Similarly, while sirolimus was genotoxic (increase of oxidized pyrimidines) to only smooth muscle cells, colchicine mainly induced oxidative damage in endothelial cells. The transcriptome analyses revealed 82 differentially expressed genes (35 with known biological functions) in the treated groups compared to control. In HCAEC, three genes (TGM3, CTSF and MTSS1L) were differently expressed after sirolimus treatment; two (SLP1 and SLC4A1) after paclitaxel; one (PAQR8) 6 h after mechanical stretching; and 19 (WBE3A, ZBTB7A, CAMK1D, OR5AP2, EME1, C3AR1, VILL, RORC, MPV17L2, CEP350, RTEL1, ATG2A, SLC38A2, SLC25A25, FOXR2,SIGLEC8, CLIC4, ATP2A2 and VPRBP) after 12 h mechanical stretching. In HCASMC, two genes (NDST4 and FZD3) were differently expressed after ...